OP0242 SAFETY PROFILE OF NINTEDANIB IN PATIENTS WITH SYSTEMIC SCLEROSIS-ASSOCIATED INTERSTITIAL LUNG DISEASE AND IDIOPATHIC PULMONARY FIBROSIS. (June 2019) - Highland, Kristin; Distler, Oliver; Gahlemann, Martina; Azuma, Arata; Fischer, Aryeh; Mayes, Maureen; Raghu, Ganesh; Sauter, Wiebke; Girard, Mannaig; Kohlbrenner, Veronika; Clerisme-Beaty, Emmanuelle; Stowasser, Susanne; et al.
Abstract : Background: Nintedanib has been investigated in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD) in the SENSCIS trial and idiopathic pulmonary fibrosis (IPF) in the two INPULSIS trials. These patient populations differ in age, sex, disease characteristics and comorbidities. Objectives: To compare the safety and tolerability of nintedanib in patients with SSc-ILD and IPF. Methods: Adverse events that occurred over 52 weeks of treatment in the SENSCIS and INPULSIS trials were assessed descriptively in subjects who received ≥1 dose of trial drug. Results: A total of 576 subjects were treated in the SENSCIS trial (288 nintedanib; 288 placebo) and 1061 in the INPULSIS trials (638 nintedanib; 423 placebo). At baseline, mean (SD) age was 54.0 (12.2) and 66.8 (8.0) years in SENSCIS and INPULSIS, respectively. The proportion of males was 24.8% and 79.3%, respectively. Over 52 weeks, 19.4% and 10.8% of patients treated with nintedanib and placebo discontinued treatment in SENSCIS, compared with 24.5% and 18.9% of patients treated with nintedanib and placebo in INPULSIS. Gastrointestinal adverse events were the most frequently reported adverse events with nintedanib and, as expected based on the underlying disease, were more frequent in patients with SSc-ILD than IPF in both treatment groups (Table). Diarrhoea adverse events were reported in 75.7% and 31.6% of patients treated with nintedanib and placebo in SENSCIS, and 62.4% and 18.4% of patients treated with nintedanib and placebo in INPULSIS, respectively. Conclusion: The safety and tolerability profile of nintedanib in patients with SSc-ILD is similar to that observed in patients with IPF. Disclosure of Interests: